2019
DOI: 10.22598/mt/2019.31.2.227
|View full text |Cite
|
Sign up to set email alerts
|

PLS Modelling of Factors Aff ecting the Cooperation Between Sales and Marketing in Pharmaceutical and Non-Pharmaceutical Manufacturing Firms

Abstract: Purpose-This paper aims to explore the manner in which cooperation between sales and marketing in pharmaceutical manufacturing companies (PMC) (n=16) and non-pharmaceutical manufacturing companies (NPMC) (n=31) is aff ected by selected indicators. It also attempts to demonstrate how the Partial Least Square (PLS) path modelling technique can reveal latent mechanisms in the interplay of the examined factors aff ecting SM cooperation. Design/methodology/approach-Data collection was carried out in the form of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The regression coefficient of conflicts was -0.136 (t=-4.10; p<0.001, SE=0.033) with regards to management culture. Table 4: Key statistics of the LVPLS model for PMC [25] External measurement models also provide important information. Rather strong correlations were found between the most important factor 'coordination' and the items in the block.…”
Section: Differences In Pmc and Npmcmentioning
confidence: 99%
See 1 more Smart Citation
“…The regression coefficient of conflicts was -0.136 (t=-4.10; p<0.001, SE=0.033) with regards to management culture. Table 4: Key statistics of the LVPLS model for PMC [25] External measurement models also provide important information. Rather strong correlations were found between the most important factor 'coordination' and the items in the block.…”
Section: Differences In Pmc and Npmcmentioning
confidence: 99%
“…In comparison, the analysis and the research model was applied to NPMC as well, however, model estimates revealed a difference as compared to the PMC model, since the key factor affecting cooperation through the management culture was not coordination but information exchange (57%) . Table 5: Key statistics of the LVPLS model for NPMC [25] Correlation of conflict and information exchange was significant (p<0.01). The two main regressions of the model were the estimation of coordination based on information exchange and vision ((R2=0.703) and the estimation of cooperation based on the other latent variables (R2=0.741).…”
Section: Differences In Pmc and Npmcmentioning
confidence: 99%